2005
DOI: 10.1111/j.1551-2916.2005.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Step Sintering of Ceramics with Constant Grain‐Size, I. Y2O3

Abstract: Isothermal and constant-grain-size sintering have been carried out to full density in Y 2 O 3 with and without dopants, at as low as 40% of the homologous temperature. The normalized densification rate follows Herring's scaling law with a universal geometric factor that depends only on density. The frozen grain structure, however, prevents pore relocation commonly assumed in the conventional sintering models, which fail to describe our data. Suppression of grain growth but not densification is consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
214
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(227 citation statements)
references
References 38 publications
11
214
0
2
Order By: Relevance
“…The optimised sintering profile adopted for the cobalt ferrite in this work is not unlike the twostep sintering approach recommended by Barba et al [4], and carried out by Kim [7] and others [5,29]. The major advantage of two-step sintering, as conceived by Chen and Wang [6], is the ability to achieve dense, nanostructured materials of grain size 25-30 nm from powders of size range 5-10 nm.…”
Section: This Intermediate Stage Of Sintering Commonly Refers To the mentioning
confidence: 99%
“…The optimised sintering profile adopted for the cobalt ferrite in this work is not unlike the twostep sintering approach recommended by Barba et al [4], and carried out by Kim [7] and others [5,29]. The major advantage of two-step sintering, as conceived by Chen and Wang [6], is the ability to achieve dense, nanostructured materials of grain size 25-30 nm from powders of size range 5-10 nm.…”
Section: This Intermediate Stage Of Sintering Commonly Refers To the mentioning
confidence: 99%
“…The sintering temperature in this region results in elimination of residual porosity without grain growth at final stage of work. Suppression of grain growth but not densification is consistent with a network of grain boundaries anchored by triple junction points, which have higher activation energy for migration than grain boundaries (Wang et al, 2006a).…”
Section: Effect Of Heating Curve In the Sinteringmentioning
confidence: 64%
“…Suppression of grain growth in the final stage of sintering was achieved by exploiting the difference between the kinetics of diffusion in the grain boundary and controlled grain boundary migration rate. Chen and colleagues used the technique of twostep sintering nanosized powders of Y 2 O 3 (Wang et al, 2006a), BaTiO 3 ferrites and Ni-Cu-Zn (Wang et al, 2006b). Other studies are reported in the literature using the two-step sintering to post nanometric TiO 2 (Mazaheri, 2008a), yttria stabilized zirconia (Mazaheri, 2008b), zirconia (Tartaj, 2009), abrasive alumina with additions of MgO-CaO-SiO 2 (Li et al, 2008), alumina-zirconia (Wang et.…”
Section: Effect Of Heating Curve In the Sinteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, increasing MA duration causes more homogeneous distribution of SiC phase in the W-matrix which contributes to higher sinter densities. On the other hand, the fact that an almost constant sintering density (∼95%) value is achieved for all W20SiC samples sintered using the second sintering regime could be attributed to slower sintering kinetics [22,23,[33][34][35] due to the "frozen" microstructure as reported in the literature [22,23,[31][32][33][34][35].…”
Section: Density Measurementsmentioning
confidence: 74%